2021
DOI: 10.1111/1365-2435.13789
|View full text |Cite
|
Sign up to set email alerts
|

Body size and shape responses to warming and resource competition

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Lastly, our results showed that the traits of both protist predators also responded to imposed experimental conditions, albeit in different ways. While size is well known to influence consumer-resource interactions ( Gilbert et al, 2014 ; DeLong et al, 2015 ; Gauzens et al, 2020 ), protist size and shape can and often do respond to foraging ( Atkinson et al, 2006 ; DeLong et al, 2014 ; Gibert et al, 2017 ; Tan et al, 2021 ), thus potentially resulting in a feedback between predator and prey phenotypes. Since the microbial communities themselves changed in structure with time and temperature, this study cannot tease apart the direct effects of temperature on protist responses from those mediated by microbial community temperature responses.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our results showed that the traits of both protist predators also responded to imposed experimental conditions, albeit in different ways. While size is well known to influence consumer-resource interactions ( Gilbert et al, 2014 ; DeLong et al, 2015 ; Gauzens et al, 2020 ), protist size and shape can and often do respond to foraging ( Atkinson et al, 2006 ; DeLong et al, 2014 ; Gibert et al, 2017 ; Tan et al, 2021 ), thus potentially resulting in a feedback between predator and prey phenotypes. Since the microbial communities themselves changed in structure with time and temperature, this study cannot tease apart the direct effects of temperature on protist responses from those mediated by microbial community temperature responses.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution of roots into the soil is of fundamental importance for a tree’s ability to both search for resources ( Yang et al, 2014 , 2017 ; Tan et al, 2021 ) and anchor to the soil ( Dumroese et al, 2019 ; Saint Cast et al, 2019 ; Montagnoli et al, 2020 ). This ability is determined by the high degree of plasticity that characterizes the root system and that represents a compromise between optimum nutrient foraging and plant mechanical stability to face external mechanical forces such as prevailing winds.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature-size rule and temperature-induced changes in community composition led to the suggestion that declining body mass may be a universal response to climate warming (Atkinson, 1994;Daufresne et al, 2009;Evans et al, 2020), although there are some emerging examples of the contrary (Gardner et al, 2011;Ruger and Sommer, 2012;O'Gorman et al, 2017). Smaller organisms can change their body size and shape in response to warming more rapidly than larger organisms due to their higher mass-specific metabolic rates and shorter generation times (Gillooly, 2000;Savage et al, 2004;Tan et al, 2021). This would result in differential temperature-size responses across trophic levels and an increase in predator-prey body mass ratios under the future warmer climate.…”
Section: Introductionmentioning
confidence: 99%